A Guideline for Sociodrama Techniques with TRINGA Values to Prevent Microaggressions among Junior High School Students - Budiyono, Alief Laili; Indreswari, Henny; Eva, Nur (Kuras Institute, 2024)
This study employs a research and development (R&D) method, specifically using the ADDIE model. The stages in this research include: (1) the analyze stage; (2) the design stage; (3) the development stage; (4) the implementation stage; and (5) the evaluation stage. The purpose of this research is to develop a socio-drama technique guide containing TRINGA (Ngerti, Ngeroso, & Ngelakoni) values and to test the effectiveness of this socio-drama technique in preventing microaggression behaviors among junior high school students. The instrument used to measure the level of microaggressions behavior is the microaggressions questionnaire, which consists of 49 valid statement items. Based on the validation results from guidance and counseling experts, instructional media experts, cultural experts, and prospective user testing, the guide has met the acceptability criteria and is highly suitable for use. Based on small group test results analyzed using the Wilcoxon test, a significance value of 0.002 < 0.05 was obtained, indicating that group guidance using the socio-drama technique with TRINGA values is effective in preventing microaggression behaviors among junior high school students. Meanwhile, the Mann-Whitney test results showed a significance value of 0.001 < 0.05, indicating a difference between the experimental and control groups. It can be concluded that the sociodrama technique incorporating TRINGA values is more effective in preventing microaggressions among junior high school students than discussion and problem-solving techniques. Future researchers are advised to incorporate other cultural values relevant to the region of the research subjects.